Interpretasi Semiotika Ferdinand De Saussure dalam Hadis Liwa dan Rayah - Habibi, M Dani (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This article is a study evaluating the Hadith interpretation in flag Rayah and Liwa or the flag of monotheism. In Indonesia, an organization that uses the banner of Tawheed is the symbol of the organization Hizbut Tahriri Indonesia. There are two warana flag that is black and white. Each of these color marked Laa illaaha illaa Allah Muhammad Messenger of God and both have a different meaning. In the context of the history of Liwa and Rayah flag used by the Prophet Muhammad and the cultural context and Rayah Liwa flag is used to establish the Khilafah state. With the legitimacy that the flag is the monotheistic flag of the Ministry of Defense so that the Indonesian Hizb ut-Tahrir organization uses the flag as a manifestation of the Khilafah Islamiyah as an ideology in the government system. Hizbut Tahrir insists that the flag Liwa and Rayah not the flag but the flag of Islam. Semiotic analysis of Ferdinand de Saussure, With semiotikanya theory consisting of four concepts, but in this study the researchers only used two concepts is the first between signifiant and signifie and both concept langue and parole. As the shape of the object flag Hizbut Tahrir and hadith texts about liwa and Rayah become the object of focus in this study.